1994
DOI: 10.1136/gut.35.7.934
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor alpha changes porcine intestinal ion transport through a paracrine mechanism involving prostaglandins.

Abstract: Prostaglandins stimulate electrogenic anion secretion and inhibit sodium chloride absorption in cryptosporidium induced pig diarrhoea. Because tumour necrosis factor a (TNFa) is an early mediator of inflammation and stimulates prostaglandin secretion, we investigated its effect on intestinal ion transport.Cryptosporidium infected pig ileum showed higher macrophage infiltration and tissue TNFa-like activity than uninfected tissues (p<005, n=4 and p<005, n=12, respectively). TNFot treatment of control porcine il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
39
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 38 publications
2
39
2
Order By: Relevance
“…In addition, we observed an association between the overproduction of TNF-␣ and more diarrheal episodes in patients with rotavirus infection, although the mechanism for this relationship is unknown. It could be due to the ability of TNF-␣ to induce increased levels of Cl Ϫ secretion in intestinal epithelial cells, as has been reported for patients with other infections or inflammatory processes (21,31). We could not identify cytokines that might mediate the expression or severity of vomiting.…”
Section: Discussionmentioning
confidence: 42%
“…In addition, we observed an association between the overproduction of TNF-␣ and more diarrheal episodes in patients with rotavirus infection, although the mechanism for this relationship is unknown. It could be due to the ability of TNF-␣ to induce increased levels of Cl Ϫ secretion in intestinal epithelial cells, as has been reported for patients with other infections or inflammatory processes (21,31). We could not identify cytokines that might mediate the expression or severity of vomiting.…”
Section: Discussionmentioning
confidence: 42%
“…Cryptosporidium infection results in intestinal structural and physiologic changes such as reduced glucose-NaCl absorption, increased chloride anion secretion (Cl Ϫ ), and epithelial barrier disruption (10,12,17,18). These alterations are known to lead to the pathogenesis of cryptosporidiosis, which includes dehydration, weight loss, diarrhea, and malabsorption.…”
mentioning
confidence: 99%
“…Lamina propria macrophages (LPMs) in the intestinal mucosa of patients with Crohn disease and ulcerative colitis are activated (24,25). Activation of LPMs results in the release of tumor necrosis factor ␣ (TNF␣) and other mediators that can directly stimulate intestinal ion transport (26,27), suggesting a role for these cells in the pathophysiology of inflammatory diarrhea. A number of recent studies have indicated that SP and its receptor may be important in the modulation and amplification of macrophage function.…”
mentioning
confidence: 99%